Effect of helicobacter pylori infection eradication on serum level of anti-tissue transglutaminase in children with celiac disease - Pejman Rohani; Maryam Monajam Zadeh; Hosein Alimadadi; Mohammad Hassan Sohouli (BMC, 2023)
Abstract Background Evidence shows the increase of anti-tissue transglutaminase (tTG) levels in various conditions, including infectious agents, independently of celiac disease (CD). The aim of this study was to investigate the effect of helicobacter pylori (H.pylori) infection eradication on serum level of tTG in children with CD. Methods This study was conducted on children aged 2 to 18 who referred to reference hospitals for diagnosis of CD. After upper endoscopy and biopsy to confirm CD and H.pylori infection, the children were divided into three groups (including group one: 16 CD patients with positive H. pylori; group two: 16 non-CD patients with positive H. pylori; and group three: 56 CD patients with negative H. pylori), respectively. The tTG level in study groups were compared after the eradication of H.pylori. Results The mean age of the subjects in the group one, two, and three was 9.7 ± 3.33, 11.8 ± 3.14, and 7.6 ± 3.32 years, respectively. Our results showed that in group one, mean tTG increased after eradication of H.pylori infection, however, these changes were not significant (182.43 vs. 157.18, P = 0.121). In the second group, although unlike the first group, mean tTG decreased after eradication of the infection, but still these changes were not significant (9.56 vs. 22.18, P = 0.449). Furthermore, at the baseline level, the mean tTG in the group three was closer to the mean tTG in the first group. Conclusion Our findings showed that the eradication of H.pylori infection does not have a significant effect on tTG levels in children with and without CD.